2020
DOI: 10.1097/mao.0000000000002879
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Cases of Inner Ear Malformation: A Novel and Simple Grading, Intracochlear EABR, and Outcomes of Hearing

Abstract: Objective: To propose a simple grading of inner ear malformation (IEM) and investigate intracochlear electrical auditory brainstem response (EABR) and outcomes for hearing in terms of the novel grading system. Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Sixty patients with IEMs who received cochlear implants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Most deaf children without malformation exhibited eV on the initial activation of the CI (19), whereas malformation ears often failed to show eV (7,8,20). The IP-2, IP-1, CC, and CND groups showed 100, 85.0, 81.8, and 54.8% of the eV-positive rate, respectively, consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most deaf children without malformation exhibited eV on the initial activation of the CI (19), whereas malformation ears often failed to show eV (7,8,20). The IP-2, IP-1, CC, and CND groups showed 100, 85.0, 81.8, and 54.8% of the eV-positive rate, respectively, consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Like pediatric CI users without malformation, objective measurements during cochlear implantation, such as electrically evoked compound action potential (ECAP) and electrically evoked auditory brainstem response (EABR), might help optimize CI stimulus in the malformation ears. ECAP was detected in only 25% of the malformed ears (5), whereas positive EABR was reported in 50% of CND cases and greater than 75% of all malformed ears (5–8), suggesting that EABR rather than ECAP is more appropriate as an objective measurement for the malformed ears. These studies used intraoperative EABR testing to predict postoperative CI outcomes but did not compare the EABR results and strength of postoperative CI stimuli in malformation cases.…”
Section: Introductionmentioning
confidence: 96%
“…Due to the limited number of cases, previous studies have reported the CI outcomes of CND patients without grouping them according to cochlear malformations (4,5,10). To take both the CN and cochlea into consideration, Minami et al (11) categorized patients into four grades according to the observation of modiolar deficiency and/or CND: grade I (present modiolus + normal CN) patients had significantly greater CAP scores than grade II (deficient modiolus + normal CN), grade III (present modiolus + CND) and grade IV (deficient modiolus + CND) patients. Approximately 7% of patients had CND combined with modiolar deficiency-type malformations, and only 25% of them achieved CAP scores of 4 or more.…”
Section: Introductionmentioning
confidence: 99%